1

**Term Test 2 / Re: Problem 3 (main sitting)**

« **on:**November 19, 2019, 09:23:37 AM »

antiderivative of u1': let e^t = u, so e^2t+1 = u^2+1, du = e^t dt, so the formula becomes integral( - 1/(u^2+1)du), which is -arctan(u) -> -arctan(e^t)

antiderivative of u2': let e^2t = u, so the formula becomes integral(2u/(u+1)), which is by chain rule: ln(u+1) -> ln(e^2t+1)

antiderivative of u2': let e^2t = u, so the formula becomes integral(2u/(u+1)), which is by chain rule: ln(u+1) -> ln(e^2t+1)